Critical Synthesis Package: Attitudes Towards Medical Communication Scale - Alisa Nagler (Association of American Medical Colleges, 2014)
Abstract Introduction This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Attitudes Towards Medical Communication Scale, and (2) a copy of the Attitudes Towards Medical Communication Scale developed by Donald Langille, MD. The Attitudes Towards Medical Communication Scale is a short 12-item evaluation. Each item consists of a statement asking individuals to indicate their level of agreement on a 5-point Likert Scale (1 = Strongly Disagree; 5 = Strongly Agree). Higher scale scores indicate a more positive attitude towards medical communication. The instrument can be utilized in paper or electronic format. It is intended as a self-assessment and used by faculty and residents but could be administered for any health care provider. If combined with other data collection, this instrument allows for association between attitudes toward provider-patient communication and respondent characteristics. The instrument developers found that interpersonal communication training improved faculty attitude towards provider-patient communication thus suggesting this as an important faculty development offering. If faculty have positive attitudes towards provider-patient communication, they may be more likely to serve as role models to learners and team members and support more formal curricula. In terms of potential limitations of the instrument and resulting outcome analysis, the developers note that faculty's assessment of communication training does not necessarily address whether trainees needs are being met. In addition, the developers found that those whose practices would traditionally seem to emphasize communication skills less, had lower response rates. The developers recommend further testing of the instrument using a longitudinal approach.